KAJIAN PEMBUATAN BRIKET BIOARANG DARI LIMBAH KULIT DURIAN DENGAN KOMBINASI SERUTAN KAYU dan TEMPURUNG KELAPA - Robert P. Langkai; Freeke Pangkerego; Herry F. Pinatik (Universitas Sam Ratulangi, 2015)
ABSTRACT The objectives of this research is to learn the proccess of making charcoal and the yield of charcoal from the waste of durian’s leather, wood’s savings, coconut shell, the combination of waste durian’s leather and wood shavings (1:1), the combination of weste durian leather and coconut shell (1:1), the combination of waste durian leather and wood shavings (2:1) and the combination of waste durian leather and coconut shell (2:1) that is the testing of briquettes burned power and residual ash which has burnt-out. This research is use complete Random Plan Method, to analyze the yield of charchoal and the time of making charcoal, briquettes burned power, the time of heating 1 litre water till it’s boil and residual ash of briquettes which has burnt-out. The result of research show that the average time of making charcoal process of waste durian leather and coconut shell is the same that is 960 seconds, while making charcoal on shavings wood has the average time 980 seconds. This case is also given the bright difference towards the result of yield charcoal. The result of briquettes burned power on seven treatment shows that the briquette of waste durian leather, coconut shell, the combination of waste durian leather and coconut shell (1:1) and the combination of waste durian leather with coconut shell (2:1) is the best because it has the quick average in heating 1 litre water that is 1140 seconds, while the quick average of burnt-out on C treatment or coconut shell briquettes that is 208,800 seconds and has briquettes rendual ash which has burnt-out is smallest that is 2.77%. Keywords : Aktif charcoal briquettes, durian lether , shavings wood and coconut shell.